2014
DOI: 10.1111/edt.12126
|View full text |Cite
|
Sign up to set email alerts
|

Over two hundred million injuries to anterior teeth attributable to large overjet: a meta‐analysis

Abstract: -Background/Aim: The association between large overjet and traumatic dental injuries (TDIs) to anterior teeth is documented. However, observational studies are discrepant and generalizability (i.e. external validity) of meta-analyses is limited. Therefore, this meta-analysis sought to reconcile such discrepancies seeking to provide reliable risk estimates which could be generalizable at global level. Material and Methods: Literature search (years 1990-2014) was performed (Scopus, GOOGLE Scholar, Medline). Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 88 publications
1
59
0
9
Order By: Relevance
“…Previous reviews report an “increased” overjet may double or triple the risk for TDI, with pooled OR estimates ranging between 2.30 and 2.61, and 2.01 and 2.31 . A study focused on Latin America and the Caribbean calculated a positive association between TDI and an overjet >5 mm, with a pooled OR of 1.98 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reviews report an “increased” overjet may double or triple the risk for TDI, with pooled OR estimates ranging between 2.30 and 2.61, and 2.01 and 2.31 . A study focused on Latin America and the Caribbean calculated a positive association between TDI and an overjet >5 mm, with a pooled OR of 1.98 .…”
Section: Discussionmentioning
confidence: 99%
“…TDIs have different presentations and are more common in children under 12 years of age . The incidence and risk of TDIs have historically been reported to be higher in individuals who have an increased overjet . Common etiological factors associated with an increased overjet include non‐nutritive sucking behaviors (NNSB), a soft tissue lip trap or a Class II skeletal relationship .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining respondents reported asking about dental trauma only with evidence of increased overjet or clinical evidence of previous dental trauma. Although an increased overjet of 3 mm or more has been shown to be associated with a twofold increase in the risk of dental trauma, such an approach carries the risk of overlooking patients with history of dental trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Accentuated overjet stands out among the few variables consistently demonstrated as risk factors for the occurrence of TDI in both the primary and permanent dentitions. A recent systematic review including children, adolescents, and adults concluded that accentuated overjet accounts for 22% of TDIs worldwide . Indeed, accentuated overjet is the most commonly identified risk/associated factor in the primary dentition ().…”
Section: Factors Associated With Tdi In the Primary Dentitionmentioning
confidence: 99%